Navigator-Guided Motion and B0 Correction of T2*-Weighted Magnetic Resonance Imaging Improves Multiple Sclerosis Cortical Lesion Detection. Issue 7 (14th July 2021) - Liu, Jiaen; Beck, Erin S.; Filippini, Stefano; van Gelderen, Peter; de Zwart, Jacco A.; Norato, Gina; Sati, Pascal; Al-Louzi, Omar; Kolb, Hadar; Donadieu, Maxime; Morrison, Mark; Duyn, Jeff H.; et al.
Abstract : Background: Cortical lesions are common in multiple sclerosis (MS). T2 *-weighted (T2 *w) imaging at 7 T is relatively sensitive for cortical lesions, but quality is often compromised by motion and main magnetic field (B0 ) fluctuations. Purpose: The aim of this study was to determine whether motion and B0 correction with a navigator-guided gradient-recalled echo sequence can improve cortical lesion detection in T2 *w magnetic resonance imaging. Materials and Methods: In this prospective study, a gradient-recalled echo sequence incorporating a navigator allowing for motion and B0 field correction was applied to collect T2 *w images at 7 T from adults with MS between August 2019 and March 2020. T2 *-weighted images were acquired in 1 to 3 partially overlapping scans per individual and were reconstructed using global average B0 correction ("uncorrected") or motion correction and spatially linear B0 correction ("corrected"). Image quality rating and manual segmentation of cortical lesions were performed on uncorrected and corrected images. Lesions seen on a single scan were retrospectively evaluated on the complementary scan. The association of cortical lesions with clinical disability was assessed. Mixed models were used to determine the effect of correction on lesion detection as well as on the relationship between disability and lesion count. Results: A total of 22 T2 *w scans were performed on 11 adults with MS (mean [SD] age, 49 [11] years; 8 women). Quality improved for 20 of 22 scans (91%) after correction. A total of 69 cortical lesions were identified on uncorrected images (median per scan, 2; range, 0–11) versus 148 on corrected images (median per scan, 4.5; range, 0–25; rate ratio [RR], 2.1; P < 0.0001). For low-quality uncorrected scans with moderate to severe motion artifact (18/22, 82%), there was an improvement in cortical lesion detection with correction (RR, 2.5; P < 0.0001), whereas there was no significant change in cortical lesion detection for high-quality scans (RR, 1.3; P = 0.43). Conclusions: Navigator-guided motion and B0 correction substantially improves the overall image quality of T2 *w magnetic resonance imaging at 7 T and increases its sensitivity for cortical lesions.